Jovens, adultos e idosos: a perspectiva do aprender e do ensinar a ler e a escrever - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2006)
Learning to read and write, for many young, adults and elderly Brazilian people means a way of meeting or reencountering with the contents that determine the ways to understand and to transform the world. The starting point of the research is the definition of the meaning of knowing to read and to write through students and teachers’ speech of young and adults literacy classes. From this starting point, to investigate until the extent this haste in the literacy process (Brazil enters in XXI century with 20 million absolute illiterates) intervenes with the conquest of this meaning of knowing to read and to write. This is because in the synthesis of the objectives that will intensify this expactation is the EJA commitment to go beyond the ways of the simple written code acquisition, or either, to teach in a way that the student can use the contents assimilated in a daily basis. Although the adult situation also includes the elder one, the research deals with the literacy challeng in the third age, in its third chapter (there are four chapters), therefore the title refers to young, adults and elderly people. Accomplishing the study, I decide to conduct a qualitative research – half-structuralized interviews and classroom observation. By inquiring, it was possible to detect the importance of the student’s valuing process through the quality of education and the investment in the teacher’s continuing education for the young and education area. Or either, to answer students and teachers successfully, instead of presenting numbers, and statistics to satisfy requirements of international organisms
Keywords: alfabetização jovens adultos e idosos; ensino; aprendizagem; young adults elderly and literacy; learning; teaching; CNPQ::CIENCIAS HUMANAS::EDUCACAO